PERBEDAAN HASIL BELAJAR, MINAT DAN MOTIVASI SISWA KELAS X SMAN 1 PALU PADA MATERI JARAK TITIK KE BIDANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN E-LEARNING DAN APLIKASI WINGEOM - Hidayat, Yayan (JSTT, 2016)
Research on application of  Cooperative Model STAD type with helped elearning and wingeom application at math has been done in class X SMA Negeri 1 Palu. This study aims to determine differences in learning outcomes, interest and motivation to learn  about  a distance of a point to the plane material  by using a model of  STAD cooperative  with helped elearning and wingeom applications. The research sample of 56 students, which is divided into an experimental group were 21 students that the class X MIA 1 and 35 students as a second experimental class, class X MIA 3, which is determined by simple random sampling technique. The method used in this study is a quasi-experiment with intact-group comparison design. Data were analyzed using descriptive and inferential analysis (t-test of two parties, one way anova and two ways anova). The results showed that there were differences in learning outcomes, interest and motivation as a result of the second treatment using with elearning and applications wingeom. This is supported by the results of data analysis showed that the differences in learning outcomes and motivation can be viewed by one factor.The conclusion of this study there are differences in learning outcomes and student motivation as a result of treatment STAD model aided elearning and wingeom applications. But for interest there is no difference.